Metropolitan Effects of a Mixed Housing Policy. The Case of ProCreAr - Elinbaum, Pablo (Editorial Pontificia Universidad Javeriana, 2018)
In recent decades, the role of the Argentine State changes from housing producer to facilitator of private sector developments. In this context, the Government launched in 2012 the program ProCreAr to alleviate the housing crisis in the country and boost the economy as a counter-cyclical measure. Considering the case of Greater Rosario, the aim of this paper is to evaluate the innovation of ProCreAr to 1) contribute and expand the theoretical frameworks on housing policies, and 2) explain their direct and indirect effects on multiple territorial scales. The main argument is that the uniqueness of ProCreAr lies in its mixed style by which compensatory and redistributive policies are combined. However, the limited scope of this “social protection” fails to influence the market of houses, land and building, producing indirect effects on urbanization processes at the local and metropolitan scale